2019
DOI: 10.1007/s10773-019-04206-4
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Application of Probabilistic Teleportation: p-Rabin Quantum Oblivious Transfer of a Qubit

Abstract: All existing quantum oblivious transfer protocols are to realize the oblivious transfer of bit or bit-string. In this paper, p-Rabin quantum oblivious transfer of a qubit (abbr. p-Rabin qubit-OT) is achieved by using a probabilistic teleportation (abbr. PT) protocol. Here, this is the first time that the concept of qubit-OT is presented. As the PT protocol is able to transfer an (un)known pure state with a certain probability, this feature makes the PT protocol well fit for Rabin OT. Furthermore, the PT protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The vast majority of quantum oblivious transfer protocols focus on a classical input-output setting, i.e., both the messages input by the sender and the elements obtained by the receiver are classical. More recently, Zhang et al [ 173 ] proposed the concept of OT with qubit messages. In their work, they present a variant of the all-or-nothing OT with an unknown qubit message.…”
Section: Further Topicsmentioning
confidence: 99%
“…The vast majority of quantum oblivious transfer protocols focus on a classical input-output setting, i.e., both the messages input by the sender and the elements obtained by the receiver are classical. More recently, Zhang et al [ 173 ] proposed the concept of OT with qubit messages. In their work, they present a variant of the all-or-nothing OT with an unknown qubit message.…”
Section: Further Topicsmentioning
confidence: 99%
“…both the messages input by the sender and the elements obtained by the receiver are are classical. More recently, Zhang et al [170] proposed the concept of OT with qubit messages. In their work, they present a variant of the all-or-nothing OT with an unkown qubit message.…”
Section: Year Authormentioning
confidence: 99%
“…In 2019, He used his proof [22] to propose a practical all-or-nothing QOT protocol [40] with a single photon, which helps researchers think another way to secure computation. Some researchers [41] only showed that their QOT is not built by a bit commitment protocol and is not covered by the MLC no-go theorem [14,15], but they did not mention Lo's no-go theorem [16].…”
Section: Introductionmentioning
confidence: 99%